The Changes in Building Spatial Functions of Dalem Joyokusuman Yogyakarta - Dwi Retno Sri Ambarwati; Tjetjep Rohendi Tohidi; Triyanto Triyanto; M. Ibnan Syarif (Universitas Negeri Semarang, 2021)
Social and cultural changes have led to changes in the condition and function of Dalem Joyokusuman, one of the houses of a close relative of the King of the Yogyakarta Kraton, which has been converted into a gallery and museum. 0The results show that judging from the changes in spatial functions, it can be seen that there are efforts to combine traditional architectural concepts into modern building concepts, namely: 1) The Spatial System is adapted to the needs of commercial space which results in a shift in the nature of space, from private to public, from sacred meaning. become profane, 2) The application of a modern functional circulation pattern, which no longer considers the hierarchy of space, 3) There is no clear boundary between business and domestic activities, with more and more space being provided for public and commercial/business activities. 4) No longer consider natural vegetation. However, even though it has undergone a change in function, in general there is no change in the structure of the main building so that the original form is maintained, in accordance with the regulations for the preservation of cultural heritage.